Die Tochter des Kraljewitsch Marko in Serwia - Djordjević-Jovanović, Jovanka (Zeitschrift für Balkanologie, 2014)
Serwia, a town in the southeast of Macedonia in Greece, developed from a Byzantine fortified settlement. Historical information about its name and ethnic composition is interwoven with legends dating back from Byzantine times. One of the surviving legends refers to a beauty in a tower as the daughter of Prince Mark (Marko Kraljević). In evidence of its intransience stands the fact that it was recorded at a time when the Slavic population had been long gone from the town. This legend, unknown to the Slavic world, was first published in 1872 in the form of a poem, its version richer in motifs appeared in 1882, and a prose variant in 1884. Variants of the poem of the beauty’s castle (κάστρο τηςωριάς) have lived in all Greek lands from Byzantines times and all the way through the Turkish period to our days. Typologically, they belong to the Akritan cycle. In terms of motifs, the poem reveals a multi-layer structure, possibly resulting from its longevity and multiple transmission. The motifs such as the castle, a young lady in the castle, beauty as a motive for war, the false monk, a ring in the dying maiden’s mouth, the milk from the maiden’s breast or the healing property of such milk, rooted in folk traditions worldwide, underwent a vernacular Christian interpretation in the poems and legends from Serwia under Ottoman rule.